Como ajudar a fidelizar clientes: o caso das lojas Quero Quero S. A . Filial de Santa Rosa - RS - Moraginski, Eclair Krüger (2001)
Deep Changes in the consuming market are demanding a high level of competitive skills from all kind of companies, mainly those directed to sales of consumer goods. How to engage customers is a key factor, a competitive skill, to be learned from successful practices. This Master dissertation is concentrated on the case of a department store, a successful branch of an organization called Quero-Quero, in south of Brazil. Observations, interviews, and a survey, and its analysis, lead to the identification of informal practices and instruments they use to establish durable links with customers. Also the role of all stakeholders is considered both in the survey and analysis.